ANTHROPOMETRY AND ACOUSTIC REVIEW AT AUDITORIUM SEAT OF GIRI NATA MANDALA CULTURE CENTER - Chintya Aridewi, Ida Ayu Anindya; Dyah Maharani, Ida Ayu; Mugi Raharja, I Gede (Universitas Telkom, 2023)
Chairs in the auditorium room are important furniture that is used for a long time by the audience. So it is important to know the anthropometric size of the auditorium seats to determine user comfort. in addition to anthropometry, auditorium chairs are used to support sound comfort. This study focuses on the anthropometry of the auditorium seats Giri Nata Mandala Puspem Badung Cultural Center and chairs as supporting the acoustic quality of the auditorium. The purpose of this study was to examine the design of auditorium seats in terms of anthropometry as well as the identification and measurement of seats in terms of interior that affect acoustics. The method used is quantitative descriptive method. Data obtained based on observation, direct measurement and dissemination of questionnaires to users. The Data were analyzed using anthropometric theory as well as theories related to interior acoustics. The results obtained are the auditorium seats have been designed in accordance with the standards of the auditorium seats with anthropometry following the standards of Indonesia. So that the chair is comfortable to use for a longtime. In terms of interior acoustics, the auditorium seats have met the standards. However, there are some inconveniences when the auditorium is used for events. Audience in the front row to the middle of the corridor on the left and right complained that the sound was too loud to make the seats shaking. In addition, vibrations in the seats are felt when other spectators pass by in the corridor. For further improvements, it would be better to pay attention to the sound volume and material of the chair or floor to reduce vibrationonthe chair. Keywords: Anthropometry, Acoustics, Auditorium Chair